2016
DOI: 10.1016/j.cognition.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of childhood bilectalism and multilingualism on executive control

Abstract: Several investigations report a positive effect of childhood bilingualism on executive control (EC). An issue that has remained largely unexamined is the role of the typological distance between the languages spoken by bilinguals. In the present study we focus on children who grow up with Cypriot Greek and Standard Modern Greek, two closely related varieties that differ from each other on all levels of language analysis (vocabulary, pronunciation, grammar). We compare the EC performance of such bilectal childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 61 publications
5
134
1
3
Order By: Relevance
“…The evidence on this point is unclear, as cognitive consequences of bilingualism have been found with similar (Spanish-Catalan: Costa et al, 2008) and different (Korean-English: Yang & Yang, 2016) languages. Studies comparing speakers of dialects have shown inconsistent results; bidialectic children who spoke Cypriot Greek and standard Greek outperformed monolingual Greek-speaking children (Antoniou et al, 2016) but studies with adults reported no difference between Italian-Venetian bidialectics and monolingual Italian speakers (Scaltritti et al, 2015) or between Mandarin-Min bidialectics and monolingual Mandarin speakers (Wu, Zhang, & Guo, 2016). In contrast to these results, however, Abutalebi et al (2015) investigated increases in grey matter density in the inferior parietal lobule in bilingual older adults and reported greater changes for bilinguals who spoke similar languages (Cantonese and Mandarin) than for those who spoke unrelated languages (Cantonese and English).…”
Section: The Mechanism Of Neuroplasticity In Bilingualismmentioning
confidence: 99%
“…The evidence on this point is unclear, as cognitive consequences of bilingualism have been found with similar (Spanish-Catalan: Costa et al, 2008) and different (Korean-English: Yang & Yang, 2016) languages. Studies comparing speakers of dialects have shown inconsistent results; bidialectic children who spoke Cypriot Greek and standard Greek outperformed monolingual Greek-speaking children (Antoniou et al, 2016) but studies with adults reported no difference between Italian-Venetian bidialectics and monolingual Italian speakers (Scaltritti et al, 2015) or between Mandarin-Min bidialectics and monolingual Mandarin speakers (Wu, Zhang, & Guo, 2016). In contrast to these results, however, Abutalebi et al (2015) investigated increases in grey matter density in the inferior parietal lobule in bilingual older adults and reported greater changes for bilinguals who spoke similar languages (Cantonese and Mandarin) than for those who spoke unrelated languages (Cantonese and English).…”
Section: The Mechanism Of Neuroplasticity In Bilingualismmentioning
confidence: 99%
“…Consequently, switching between languages may require little cognitive effort and control, and as a result, does not lead to the supposed training effect. Various other studies in which the bilinguals are also immersed in both the minority language and the state’s official language do show cognitive effects of bilingualism: balanced Frisian-Dutch children outperform Dutch-dominant children (Bosma et al, 2017), and Spanish-Catalan bilinguals (Costa et al, 2008, 2009; Hernández et al, 2013), Sardinian-Italian bilingual children (Lauchlan et al, 2013; Garraffa et al, 2015) and children who speak Cypriot Greek and Standard Modern Greek (Antoniou et al, 2016) outperform Spanish, Italian, and Greek monolinguals, respectively, on tasks testing executive functioning. It is possible that the participants in these studies are less bilingually fluent than the Basque-Spanish and Welsh-English bilinguals who showed no cognitive effects of bilingualism, because being immersed in the two languages does not necessarily imply fluent bilingualism.…”
Section: Introductionmentioning
confidence: 96%
“…Further research currently carried out under the first author's supervision investigates other aspects of bilectal grammar aiming to tie these to closer to both executive control abilities [cf. Antoniou et al (2016), but also Garraffa et al (2015)] and, more generally, a gradient scale of multilingualism (cf. Grohmann, 2014b;Grohmann and Kambanaros, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The starting point of efforts exploring the "cognitive advantage" of bilectal children from Cyprus reported in the study by Antoniou et al (2016) comes from the original findings on clitic placement by young school-age children (Grohmann, 2011), which has subsequently been researched with many more child populations and groups [summarized in the study by Grohmann (2014a)]. This article constitutes a comprehensive overview of the reported data with a novel statistical approach.…”
Section: Toward Capturing the Socio-syntax Of Development Hypothesismentioning
confidence: 99%